The Aesthetic of Employing the Ornamental Units and the Arabic Letter in the Design of the Women’s Fashion Clothes - Salim Muhammed , Hanadi (Journal of College of Education, 2019)
The arts in its varieties consider one of the important expression means about the human needs and interests as a result of spiritual and psychological human needs to the beauty. Since the human started inspired the meaning of the beauty and its images in the universe in general and the surrounding environment in special and the subject sense in it, then began reflex it as an aesthetic production. As an example; the man of cave was expressed about the things see them and tried to imitate them by drawing in any of his primitive methods which expressed on the senses and thoughts. The research aims to realize the means of employing the Islamic ornamental units and Arabic letter in design of the women’s clothes and clearing on their beauty. The researcher depended on the descriptive analyzing method in creating the research procedures because it is the most scientific method suitable to achieve the aim of the research. The current research comprised on studying and analyzing the designs of women’s clothes in the field and exploratory reality that the researcher obtained through them some group of designs were presented on the public markets of Baghdad in order to achieve the aim of the study. So, it is surveyed (52) samples of designs for women’s fashion clothing and selected (4) samples are common in the public markets from the imported clothes target the women group represented in percentage of (8%). The researcher designed the application of analyzing including the samples depending on the hypothetical section from indications comprised on the themes then became basic paragraphs concerned in the clothing design of women’s fashion and they connected with the research to fulfillment to achieve the aim of the research. The research concluded some results such as: The units of ornaments used in design of the women’s clothing have an apparent role in giving the out qualities of cloth because they give kind of aesthetic and expressive varieties for the parts of the design. The colours are employed by the cloth’s designer played an essential role in presenting the beauty of the ornamental and geometrical designs to the cloth that achieved kind of symbolic, aesthetic, and functional dimensions